Comparison of the frequency and phenotypic profile of Mycobacterium tuberculosis-specific CD4 T cells between the site of disease and blood in pericardial tuberculosis - Du Bruyn, Elsa; Ruzive, Sheena; Howlett, Patrick; Cerrone, Maddalena.; Jacobs, Ashley J.; Arlehamn, Cecilia S. Lindestam; Sette, Alessandro; Sher, Alan; Mayer-Barber, Katrin D.; Barber, Daniel L.; Mayosi, Bongani; Ntsekhe, Mpiko; et al. (Frontiers in Immunology, 2022)
Studies of the immune response at the site of disease in extra-pulmonary tuberculosis (EPTB) disease are scarce. In this study, we compared the cellular profile of Mycobacterium tuberculosis (Mtb)-specific T cells in pericardial fluid and peripheral blood in patients with pericardial TB (PCTB). Whole blood and pericardial fluid (PCF) samples were collected at the time of diagnostic sampling, with repeat blood sampling after completion of anti-tubercular treatment (ATT) in 16 PCTB patients, most of them being HIV-1 infected (n=14). These samples were stimulated ex vivo and the phenotypic and functional cellular profile of PCF and blood was assessed by flow cytometry. We found that lymphocytes were the predominant cell type in PCF in PCTB, with a preferential influx of CD4 T cells. The frequencies of TNF-α producing Mtb-specific granulocytes and Mtb-specific CD4 T cells were significantly higher in PCF compared to blood. Mtb-specific CD4 T cells in PCF exhibited a distinct phenotype compared to those in blood, with greater GrB expression and lower CD27 and KLRG1 expression. We observed no difference in the production IFNg, TNF or IL-2 by Mtb-specific CD4 T cells between the two compartments, but MIP-1β production was lower in the PCF T cells. Bacterial loads were not associated with alterations in the phenotype or function of Mtb-specific CD4 T cells. Upon ATT completion, HLA-DR, Ki-67 and GrB expression was significantly decreased, and relative IL-2 production was increased in peripheral Mtb-specific CD4 T cells. Overall, using an ex vivo assay to compare the immune response towards Mtb in PCF and in blood, we identified significant difference in the phenotypic profile of Mtb-specific CD4 T response between these two compartments. Moreover, we show that the activation profile of peripheral Mtb-specific CD4 T cells could be used to monitor treatment response in PCTB.